Clinical and Radiological Outcome of Posterior Cervical Fusion Using Philips AlluraXper FD20 Angiography Suite - Armando Dolp; Abdussalam Khamis; Javier Fandino; Jenny C. Kienzler (Brain Sciences)
Background: Posterior cervical fusion (PCF) is widely used for cervical spinal cord decompression with/without fusion. In our hybrid operating room, intraoperative computed tomography (iCT) is routinely used to verify screw placement. This study analyzed clinical and radiological outcomes after PCF and evaluated iCT benefits for detecting screw misplacement. Methods: Nineteen patients underwent PCF between March 2012 and April 2016 for degenerative (n = 6), neoplastic (n = 7), and traumatic (n = 6) conditions. Seven patients had primary PCF, while twelve underwent PCF following anterior fusion due to segmental instability with cervical malalignment (n = 11) or tumor progression (n = 1). Results: The mean patient age was 59 ± 11 years, with 63% male patients. The median follow-up was 21 months. PCF averaged 4.74 segments (range: 1–9). At follow-up, 79% reported pain improvement and normal sensorimotor function. Of six patients with preoperative paresis, five showed improved muscle strength. No persistent gait disturbances occurred. Complications requiring revision occurred in four patients (21%): three surgical site infections and one cerebrospinal fluid leak. One perioperative death occurred (5%). iCT detected incorrect screw placement in seven patients (36%), allowing the immediate repositioning of eight screws, preventing later revision surgeries. The overall fusion rate was 92%. Conclusions: PCF with iCT is safe and effective for various cervical spine pathologies, yielding good long-term clinical outcomes. iCT effectively detects and enables immediate correction of screw malposition, reducing revision surgery needs. This imaging modality demonstrates high sensitivity and specificity for identifying clinically relevant screw malpositions.